Current Applied Science and Technology Annual Report 2023 - Assoc. Prof. Dr. Dusanee Thanaboripat (Current Applied Science and Technology, 2024)
Current Applied Science and Technology journal published 90 articles in Vol. 23 Nos. 1-6. Figure 1 show details of comparison of submission, acceptance rate (%) and rejection rate (%) during 2020-2023. It can be seen that the rejection rate is increased due to an increase of manuscripts submitted. The acceptance rate and the rejection rate do not include “in process” and withdrawn manuscripts. A decline after pre-screening and after review are counted as the rejection rate. The top ten countries of authors submitting manuscripts to be published in the journal in 2023 are shown in Figure 2. The top three countries are Thailand, India and Indonesia. Figure 3 shows numbers of published articles from KMITL, other organizations in Thailand and overseas. For KMITL, School of Science published the most numbers (29 articles), followed by School of Agricultural Technology (8 articles) and College of Materials Innovation and Technology (7 articles). For other organizations in Thailand (except KMITL), King Mongkut’s University of Technology Thonburi published the most (12 articles), followed by Mahasarakham University (11 articles) and Silpakorn University (9 articles). When the average duration process for publication during 2021-2023, as shown in Figure 4, are compared, it is found that the process time in 2023 is shorter than in 2022. For citation, Category and CiteScore rank in Scopus are presented in Table 1. For CiteScore rank in the year 2023, there are three subcategories in Q3, i.e. Agricultural and Biological Sciences (miscellaneous), Agronomy and Crop Science and Environmental Engineering.
Keywords: Academic Publishing and Open Access; Academic Writing and Publishing; Fisheries and Aquaculture Studies